The Hazards of Microplastics: A Legal Perspective on Unlawful Acts and Consumer Protection - Aufa, Muhammad Fikri; Abdillah, Irvan; Saifuddin, Sendy Salsabilla; Apriana, Adistia Lulu (CV. Strata Persada Academia, 2025)
Microplastics have emerged as a multidimensional threat, not only to environmental and public health but also to legal systems worldwide. Despite increasing scientific evidence regarding their ecological persistence and toxicity, legal responses—particularly in civil law and consumer protection—remain underdeveloped. This study examines the legal implications of microplastic pollution through the lens of unlawful acts (onrechtmatige daad) and consumer protection, using normative legal research methods grounded in statutory analysis, legal doctrine, and jurisprudence. The findings reveal that industrial negligence in plastic waste management may satisfy the legal elements of tort under Indonesian civil law (Article 1365 of the Civil Code), especially when microplastics harm ecosystems or pose health risks to consumers. Moreover, the absence of specific regulatory frameworks addressing microplastic content in consumer products indicates a critical normative gap that undermines the right to product safety and accurate information. This research argues that microplastic pollution constitutes not merely a technical or scientific issue but a legal crisis demanding comprehensive reform. It recommends integrating the precautionary principle into national legislation, setting enforceable safety standards, mandating microplastic content labeling, and enhancing producer accountability, drawing lessons from international instruments. The study also advocates for the establishment of independent testing bodies and robust monitoring mechanisms to support scientific evidence in environmental litigation.